Фотоіндуковані зміни поглинання та двопроменезаломлення в складних халькогенідних кристалах AgxGaxGe1-xSe2 (0,167 ≤ x ≤ 0,333) - Кітик, Іван; Мирончук, Галина; Замуруєва, Оксана; Kityk, Ivan; Myronchuk, Galyna; Zamuruyeva, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2013)
Четвертинні монокристали AgxGaxGe1-XSe2 (х = 0,333, 0,250, 0,200 і 0,167) були вирощені методом Стокбаргера Бріджмена. Досліджено спектральні залежності фотоіндукованого поглинання в нелегованих кристалах селеніду при опроміненні лазерними імпульсами з довжиною хвилі 808 нм. Представлено динаміку фотоіндукованого оптичного поглинання AgGaGe3Se8:Cu під вливом 532 нм та 1300 нм лазерного випромі- нювання CW.; Quaternary crystals AgxGaxGe1- XSe2 (x = 0.333, 0.250, 0.200 and 0.167) were grown by Bridgman Stockbarger. Spectral dependence of photoinduced absorption in undoped selenide crystals irradiated laser pulses with a wavelength of 808 nm. The dynamics of photoinduced optical absorption AgGaGe3Se8: Cu at 532 nm poured and 1300 nm laser CW. The changes of the birefringence demonstrate substantial changes of time kinetics depending on the pumping wavelengths. It was found that the changes of the photoinduced birefringence are at least 4 times higher for the 532 nm pumping wavelength with respect to the 1300 nm wavelength. The Ag cations, Cu dopants and local trapping levels play here crucial role.
Photoinduced Absorption and Birefringence Changes in Complex Chalcogenide Crystals AgxGaxGe1-xSe2 (0,167 ≤ x ≤ 0,333)
Keywords: фотоіндуковане поглинання; двопроменезаломлення; метод Сенармона; анізотропія; photoinduced absorption; birefringence; method Senarmona; anisotropy